Poems Of Whitman: A Complete Reflection Of American Consciousness - Mostafa Faruk Ahamed, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The first step of Walt Whitman in the field of American literature has passed two hundred years. Obviously, it is a long time but still fresh, alive, and vibrantly young. He is, in fact, one of the great poets who is not just a poet but also a great man who has become a symbol of national consciousness by his pursuit and courage. In his poetry, the philosophy of American great independence has become an idol. He exerts his vitality, innovative style, and national mindset in his poetry so much that any discussion on American literature cannot proceed without reading his poetry. A literary critic, Harold Bloom, at the inaugural ceremony of the 150th Anniversary of the Leaves of Grass wrote "If you are an American, Walt Whitman is your psychological father and mother" (Harold, 2005, p.12). His personal zeal and conscious attempt to break the tradition has made him one of the leading American romantic poets. To him, the role of common people is important to build America. In other words, American consciousness is the main content of his poetic philosophy. This paper focuses on showing how his American consciousness is reflected in some of his poems while analyzing some specific lines of those poems.